Impact of Intensive Lifestyle Intervention on Neural Food Cue Reactivity: Action for Health in Diabetes Brain Ancillary Study. Issue 7 (21st May 2019) - McDermott, Kathryn Demos; Williams, Samantha E.; Espeland, Mark A.; Erickson, Kirk; Neiberg, Rebecca; Wadden, Thomas A.; Bryan, R. Nick; Desiderio, Lisa; Leckie, Regina L.; Falconbridge, Lucy H.; Jakicic, John M.; Alonso‐Alonso, Miguel; et al.
Abstract : Objective: The Action for Health in Diabetes (Look AHEAD) research study was a randomized trial comparing the effects of an intensive lifestyle intervention (ILI) versus a diabetes support and education (DSE) control group in adults with type 2 diabetes and overweight or obesity. Functional magnetic resonance imaging was used to determine whether neural food cue reactivity differed for these groups 10 years after randomization. Methods: A total of 232 participants (ILI, n = 125, 72% female; DSE, n = 107, 64% female) were recruited at three of the Look AHEAD sites for functional magnetic resonance imaging. Neural response to high‐calorie foods compared with nonfoods was assessed in DSE versus ILI. Exploratory correlations were conducted within ILI to identify regions in which activity was associated with degree of weight loss. Results: Voxel‐wise whole‐brain comparisons revealed greater reward‐processing activity in left caudate for DSE compared with ILI and greater activity in attention‐ and visual‐processing regions for ILI than DSE ( P < 0.05, family‐wise error corrected). Exploratory analyses revealed that greater weight loss among ILI participants from baseline was associated with brain activation indicative of increased cognitive control and attention and visual processing in response to high‐calorie food cues ( P < 0.001, uncorrected). Conclusions: These findings suggest there may be legacy effects of participation in a behavioral weight loss intervention, with reduced reward‐related activity and enhanced attention or visual processing in response to high‐calorie foods.